Learning to code: interplay of attitude, emotions, and fun. - Tisza, Gabriella; Markopoulos, Panos; Bekker, Tilde (Humanities & Social Sciences Communications, 2023)
There is a worldwide pursuit to increase children's interest in STEM (Science, Technology, Engineering, Mathematics) especially in computer science through extra-curricular activities such as coding workshops, hackathons, and FabLab initiatives. However, the underlying reasons for children's willingness for participation in such activities, and the effect of participation on children's topic-related knowledge are still not well understood. In order to understand the factors influencing children's attitude about programming and investigate what effects children's learning during such activities, we designed a workshop for introducing primary school children to programming, and implemented it for a Dutch primary school class (n = 23) as an exploratory case study. We recorded their attitudes towards programming, their state-level emotions, the fun they experienced, and the initial- and final knowledge on the topic and their gender for comparative purposes. Our findings indicate that the coding workshop had a positive effect on children's state-level emotions, as children felt significantly happier, more excited and more in control at the end of the workshop than at the beginning of it. We also found that children's attitude toward programming changed significantly and positively during the workshop, and that children's attitude about programming is influenced by the experienced fun while learning to code regardless their gender. Additionally, we found that the workshop was successful in terms of knowledge acquisition: both the measured and the reported learning indicate that children learned during the activity. Our findings also indicate that children's reported learning has a positive association with their state-level emotion feeling in control and that the measured learning is negatively influenced by high levels of stress. Accordingly, our results draw attention to the downshifting effect of high arousal emotions on the measured learning. Throughout the paper we discuss gender differences along the study findings and elaborate on further practical implications.